Extracranial carotid artery wall abnormalities in patients with acute ischemic stroke - Nunavath, Akhilesh Kumar; Manorenj, Sandhya; Jawalkar, Srikant (International Journal of Research in Medical Sciences, 2022)
Background: Stroke is the second most common cause of mortality worldwide. Large artery extracranial atherosclerosis is one of the major causes of ischemic stroke. The present study laid emphasizes on causal relationship between the carotid wall abnormalities and occurrence of ischemic stroke. The aim and objectives of the study were to estimate the prevalence of carotid artery wall abnormalities in acute ischemic stroke patients and assessment of association between carotid wall abnormalities and vascular risk factors. Methods: A cross-sectional observational study was conducted in department of neurology for a period of two years. Cases with acute ischemic stroke were included in the study. Carotid Intima media thickness (CIMT) was measured using carotid duplex ultrasound scanning at the level of carotid bifurcation. Results: CIMT findings was abnormal in 87% of cases where the thickness was ≥0.8 mm. 38% of patients with Ischemic stroke had CIMT ≥1.2 mm. Mean CIMT was highest in patients with sedentary life style (CIMT-1.18 mm) and the differences were significant when compared to non-sedentary life style group. CIMT values were higher in patients with age 61-80 years (CIMT: 2.1 mm); with multiple vascular risks like diabetes and hypertension (CIMT: 1.16 mm); with diabetes mellitus alone (CIMT: 1.14 mm) and hypertension alone (CIMT-1.13 mm) respectively. Conclusions: Highest mean CIMT value were observed in older adults with age range of 61 to 80 years. Individuals with sedentary life style habits and multiple vascular risk factors had higher mean CIMT value. Early identification of abnormal CIMT value combined with appropriate treatment can prevent stroke in future.